2012
DOI: 10.3329/uhj.v8i1.11666
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Venous Disease –Management Update

Abstract: Not available DOI: http://dx.doi.org/10.3329/uhj.v8i1.11666 University Heart Journal Vol. 8, No. 1, January 2012

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The first line of treatment at early signs of venous disease should include the following: Avoiding long periods of standing or sitting. Intermittent elevation of the legs during the day and elevation of the legs at rest. While sitting, ideally the legs should be above the thigh – this reduces the pressure within the veins. It is suggested that raising the legs above the level of the heart for 15 to 30 min at various stages throughout the day can dramatically help reduce the pressure …”
Section: Conservative Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first line of treatment at early signs of venous disease should include the following: Avoiding long periods of standing or sitting. Intermittent elevation of the legs during the day and elevation of the legs at rest. While sitting, ideally the legs should be above the thigh – this reduces the pressure within the veins. It is suggested that raising the legs above the level of the heart for 15 to 30 min at various stages throughout the day can dramatically help reduce the pressure …”
Section: Conservative Treatmentsmentioning
confidence: 99%
“…Three classes of stocking are generally used. Grade 1 are the lower‐pressure stockings, usually between 20 and 30 mmHg and are predominantly used in legs that are prone to lateral phlebectasia (or vein dilation) and oedema . For the treatment of dermatitis or ulcers, generally class 2 or class 3 stockings are used.…”
Section: Conservative Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations